Interactivity in learning instructional videos: Sending danmaku improved parasocial interaction but reduced learning performance - Mou, Ya; Jing, Bin; Li, Yichun; Fang, Nanyang; Wu, Changcheng (Frontiers in Psychology, 2022)
Introduction The instructional video is considered to be one of the most distinct and effective virtual learning tools. However, one of its biggest drawbacks is the lack of social interaction that occurs. This study tested the impact of participants sending zero danmaku (sending messages on the screen), three danmaku sending, and unlimited danmaku as an instructional video plays on learning performance. Methods We assessed learners’ retention and transfer scores, as well as self-report scores for cognitive load and parasocial interaction. This study sample comprised 104 participants who were randomly assigned to learn from one of three instructional videos on the topic of the heart. Results The results showed that sending danmaku improved learners’ parasocial interaction, while significantly increasing their cognitive load and also hindering learning performance. The observed increase in cognitive load reported by learners was also caused by increased levels of parasocial interaction. Discussion Our findings suggest that by sending danmaku, learners can promote interactive learning, but that this has a negative impact on learning performance and the process of video learning.